SIFAT ANTI RAYAP DARI EKSTRAK IJUK AREN (Arenga pinnata Merr.) - Astuti Arif; M. Natsir Usman; Fatmawaty Samma (Forestry Faculty of Universitas Hasanuddin, 2007)
The fiber of sugar-palm tree Arenga pinnata Merr., locally known as ijuk, is frequently harvested after the tree age of 5 years and traditionally used as covering to protect ground-contact wood construction materials against organism attack, particularly subterranean termites. The effectiveness of sufar-palm tree fiber extract of marketed formation using acetone and and hexane againts subterannean termites (Coptotermes sp.) has been observed. The results showed that mortality of termite after 2 weeks is 100% on samples given the sugar-palm tree fiber extract, compared with the mortality of controls (without sugar-palm tree fiber extract) is 7,07% after 3 weeks. The consumption rate of termites opposited with the mortality value, due to the existence of bioactive components or chemical compounds having inhibitor or toxic against termites activities. Key words: Sugar-Palm Tree Fiber, Arenga pinnata, Antitermiticidal activities, Coptotermes sp.